The TOR Data Communication System - Haraty, Ramzi A. (2014)
Since the day the Internet became a common and reliable mechanism for communication and data transfer, security officers and enthusiasts rallied to enforce security standards on data transported over the globe. Whenever a user tries communicating with another recipient on the Internet, vital information is sent over different networks until the information is dropped, intercepted, or normally reaches the recipient. Critical information traversing networks is usually encrypted. In order to conceal the sender's identity, different implementations have proven successful ¿ one of which is the invention of anonymous networks. This paper thoroughly investigates one of the most common and existing techniques used during data communication for avoiding traffic analysis as well as assuring data integrity ¿ the onion router (TOR). The paper also scrupulously presents the benefits and drawbacks of TOR.